2015
DOI: 10.1007/s10562-015-1522-7
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel Preparation of Samaria Catalysts for the Oxidative Coupling of Methane

Abstract: A new sol-gel synthesis route for aluminasamaria mixed aero-and xerogel catalysts based on the socalled epoxide addition method and the use of these systems as catalysts for the oxidative coupling of methane (OCM) is reported. As precursors simple chloride or nitrate salts can be used. The mesoporous materials are X-ray amorphous even after calcination to 800°C and show an intimate mixing of Al and Sm on the nanoscale. In the case of the xerogels derived from chlorides, C 2 yields comparable to pure samaria ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…The specific surface areas are rather small; e. g. Neumann et al . synthesized Sm 2 O 3 ‐Al 2 O 3 xerogels by a similar route and achieved specific surface areas as high as 117 m 2 /g.…”
Section: Resultssupporting
confidence: 89%
“…The specific surface areas are rather small; e. g. Neumann et al . synthesized Sm 2 O 3 ‐Al 2 O 3 xerogels by a similar route and achieved specific surface areas as high as 117 m 2 /g.…”
Section: Resultssupporting
confidence: 89%
“…Direct comparison is not possible due to the different catalyst bed lengths, however nanosphere and nanofiber morphologies showed higher activity and selectivity than any other catalysts especially at lower temperatures (<540 °C) and at high space velocity. Sm 2 O 3 catalyst with hollow nanosphere morphology showed 10.5 % C 2 yield and 5.5 % C 2 H 4 yield at 450 °C under 120.000 L kg −1 h −1 space velocity which was higher than many Sm 2 O 3 catalysts in the literature [11,29,31] …”
Section: Resultsmentioning
confidence: 76%
“…Sm 2 O 3 catalyst with hollow nanosphere morphology showed 10.5 % C 2 yield and 5.5 % C 2 H 4 yield at 450°C under 120.000 L kg À 1 h À 1 space velocity which was higher than many Sm 2 O 3 catalysts in the literature. [11,29,31] Lastly, in order to confirm the effect of specific surface area and investigate the effect of reaction temperature an additional activity test was performed for Sm 2 O 3 -np and Sm 2 O 3 -nf catalysts using the same catalyst bed volume (0.2 ml) and the same GHSV (500 h À 1 ). It was observed that the activity, selectivity and yield (Figure 13-16) were higher for Sm 2 O 3 -np than Sm 2 O 3 -nf at the same feed and catalyst bed temperatures which showed that the specific surface area was the primary parameter that affects the reaction performance.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained solid is referred to as an aerogel and typically possesses less agglomeration of particles, smaller particle size, higher porosity and higher surface area compared to the corresponding xerogel [56][57][58][59]. Sol-gel processes followed by scCO2 drying have been reported extensively for the production of silica [60] and single metal oxide aerogels (such as Al2O3 [61], TiO2 [10], ZrO2 [62], WO3 [8], ZnO [5], Cr2O3 [6], Fe2O3 [63], MoO3 [64]), doped metal oxide aerogels (such as N-TiO2 [65], Nb, Ta, and V-doped TiO2 [66], Ni-Al2O3 [67,68]), mixed oxide aerogels (such as TiO2-SiO2 [69], V2O5-TiO2 [70], ZnO-SnO2 [71], Al2O3/Sm2O3 [72]), as well as nanoparticles supported on oxide aerogels (such as Ag/Cu-ZrO2 [73] and Pt/Co-Al2O3 [74]). The process of supercritical drying of gel involves the replacement of molecules entrapped in the pores by either liquid CO2 or scCO2, and subsequent supercritical drying in a simple batch reactor (as seen in Figure 6).…”
Section: Combination Of Sol-gel Methods and Scco2 Drying To Produce Amentioning
confidence: 99%
“…The activation and conversion of CH 4 into higher hydrocarbons would open valuable pathways to produce chemicals which currently are obtained from cracking and refining of crude oil [86]. Neumann et al reported the oxidative coupling of CH 4 to produce ethane and ethylene along with CO and CO 2 as undesired side products employing Sm 2 O 3 /Al 2 O 3 as the catalyst [72]. The Sm 2 O 3 /Al 2 O 3 material was prepared via a sol-gel process in the presence of an epoxide (the function of the epoxide was discussed in Section 3.1) and ensuing scCO 2 drying.…”
Section: Chemocatalytic Oxidation Of Organic Compoundsmentioning
confidence: 99%